In situ formation of surface and bulk oxides in small palladium nanoparticles. Issue 86 (23rd September 2020) - Bugaev, Aram L.; Zabilskiy, Maxim; Skorynina, Alina A.; Usoltsev, Oleg A.; Soldatov, Alexander V.; van Bokhoven, Jeroen A.
Abstract : Evolution of surface and bulk palladium oxides in supported palladium nanoparticles was followed in situ using X-ray absorption spectroscopy. Abstract : Evolution of surface and bulk palladium oxides in supported palladium nanoparticles was followed in situ using X-ray absorption spectroscopy. The surface oxide was found to be easily reducible in hydrogen at room temperature, while removal of bulk oxide required heating in hydrogen above 100 °C. We also found that the co-presence of hydrogen and oxygen favours a stronger oxidation of palladium particles compared to pure oxygen.